Impact of language-augmented human capital on foreign direct investment: a study of developing countries - Wilson, O. C. S.; Premagowrie, Sivanandan; Abdul Hamid, Baharom; Habibullah, Muzafar Shah (South Asian Academic Research Journals, 2016)
Foreign direct investment is regarded as a key element in globalization and international economic integration. Being an additional source of investment funding, it plays an integral role in the economic development of countries. This study investigates the relationship between English language proficiency and foreign direct investment in developing countries. The study used macro and socio-economic variables of foreign direct investment, level of English language proficiency, income per capita and unemployment. A sample of forty-nine (49) developing countries is used. The model was regressed cross-sectionally and White standard error was employed to remove traces of heterogeneity. As expected, it is found that there are significant relationships between (1) English language proficiency and foreign direct investment; and (2) income per capita and foreign direct investment. The results confirmed the importance of English language proficiency in attracting foreign direct investment into developing countries. It also provides some insights to designing of policies mainly to raise the level of human resources capabilities in terms of improved language proficiency to facilitate sustainable flows of investment from abroad.